Towards Liberating Education: A Proposed Rights-based Instructional Planning Approach for Teaching Higaonon Learners in the Philippines - Ernesto Jr. Bastida; Maria Ana Quimbo; Ruth Ortega-Dela Curuz; Evelie Serrano; Merlyne Paunlagui; Edmund Centeno (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
This study proposes a rights-based instructional planning approach for teachers serving indigenous learners, particularly those assigned to schools in Higaonon communities (IPEd). The content of the paper focuses on the following:(1) assumptions about Higaonon indigenous learners; (2) components of the right-based instructional planning approach; and (3) facilitating and hindering factors that may affect the implementation of the right-based instructional planning approach. The researcher used an exploratory research design to develop the proposed planning approach. It was conducted in Higaonon communities in the Municipality of Esperanza, Agusan Del Sur, Philippines. The responses of the selected school officials, IPEd teachers, Higaonon tribal leaders, parents, students, and external stakeholders. The responses of the selected school officials, IPEd teachers, Higaonon tribal leaders, parents, students, and external stakeholders. This paper strongly believes that shifting from a culture-based to right-based IPEd teaching approach is expected to lay down positive changes in all aspects of life for indigenous learners, including social, economic, education, civic, and political, as they begin to understand and protect the inherent rights to ancestral domains, cultural integrity, self-governance, and social justice which are accounted for them. The early inculcation of Indigenous Peoples Rights Act (IPRA) law into their identity formation through school curriculum is projected to eradicate all forms of discrimination, exclusion, alienation, disintegration, and vulnerabilities in mainstream societies.